Pendidikan Kesehatan tentang Bahaya Narkoba pada Remaja di Panti Sosial Bina Anak Wanita dan Eks Psikotik (PSBAWEP) Harapan Mulya Provinsi Jambi - Rahmadhani, Dwi Yunita; Yesni, Marnila; Mayenti, Fitra; Permanasari, Ika; Suri, Marta (Universitas Baiturrahim, 2025)
Adolescence is a period of human development. This period is a period of change or transition from childhood to adulthood which includes biological changes, psychological changes, and social changes, adolescence is closely related to trying new things that they think can make them stand out in their associations such as smoking, trying drinking, free sex and drug use (Irianto, 2014). Abuse of Narcotics, Psychotropics and Other Active Substances (Drugs), is a problem whose development is very concerning. Viewed from the social aspect, this problem does not only affect people with problems, but also has an impact on families, the social environment and can even threaten and endanger the future of the nation and state (Madania, 2014). Therefore, community service activities aim to increase the knowledge of teenagers by providing information about the dangers of drugs. This activity will be held in April 2022 at the Panti Sosial Bina Anak Wanita and former psychotics of Jambi Province. The target in this activity is the poor, poor and neglected teenagers in Jambi Province. A total of 17 participants. A total of 14 of them already know about the dangers of drugs for health and in carrying out daily activities because they can damage organ function, one of which is the brain. Provide health education about the dangers of drugs to adolescents at the Harapan Mulya Women's and Ex-Psychotic Child Development Social Home (PSBAWEP) Jambi Province. This is an effort of health workers to improve the health status of adolescent girls and women through health education as the nation's next generation. Health education is also an effort to protect and remind the children and women of the nation's successors not to fall into the dangers of drugs. Always anticipate what is consumed, socialize around the place of residence and strengthen each other's faith. The output of this service activity is an increase in knowledge about the dangers of drugs so that teenagers can live healthy and independent lives without drugs and publications in national journals.